UPAYA PENGEMBANGAN MORAL APARATUR PEMERINTAH DALAM MEWUJUDKAN GOOD GOVERNANCE - Yasminingrum S.H., M.H. (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2014)
The demands upon democracy and development discourse on good governance bring government officials for also must accommodate new challenges. The development of government officials should be initiated from leader level who can build the importanceof moral. Moral development of the government officials for creating good governance to reduce bureaucracy demoralization and public policy manipulation should be showed on the public satisfaction and warranty that governance and democracy are useful, equivalent and effective for the public interest. Good governanceimplementation requires capacity dimensions which in this time tends to be ignored and only pay less attention is moral things.